Location Matters: An Examination of Trading Profits - Hau, Harald (Journal of Finance, 2001)
ABSTRACT The electronic trading system Xetra of the German Security Exchange provides a unique data source on the equity trades of 756 professional traders located in 23 different cities and eight European countries. We explore informational asymmetries across the trader population: Traders located outside Germany in non‐German‐speaking cities show lower proprietary trading profit. Their underperformance is not only statistically significant, it is also of economically significant magnitude and occurs for the 11 largest German blue‐chip stocks. We also examine whether a trader location in Frankfurt as the financial center, or local proximity of the trader to the corporate headquarters of the traded stock, or affiliation with a large financial institution results in superior trading performance. The data provide no evidence for a financial center advantage or of increasing institutional scale economies in proprietary trading. However, we find evidence for an information advantage due to corporate headquarters proximity for high‐frequency (intraday) trading.